Population pharmacokinetics of amikacin in neonatal intensive care unit patients - Caceres Guido, Paulo Arturo (2017)
Background Amikacin treatment requires close monitoring of blood concentrations to increase the probability that levels achieved are both effective and safe. Aims We described population pharmacokinetics parameters of amikacin in newborns from a Neonatal Intensive Care Unit with suspected or documented sepsis. Methods A nonlinear mixed-effect model approach was used to analyse the data. Results Twenty seven neonates were enrolled. Final parameter estimates were: Ke(h-1)=0.232x(CR) Exp-0.85; V(mL/kg)=497. Conclusion Weight and serum creatinine are associated with neonatal amikacin volume of distribution and elimination constant rate, respectively. The presence of sepsis may decrease amikacin elimination, although this observation should be further explored. These results could help to individualize amikacin dosage for neonates.